Recent Advances in Identifying Biomarkers and High-Affinity Aptamers for Gynecologic Cancers Diagnosis and Therapy - Xiaoqun Ma; Thangavel Lakshmipriya; Subash C. B. Gopinath (Journal of Analytical Methods in Chemistry)
Cancer is the uncontrollable abnormal division of cell growth, caused due to the varied reasons. Cancer can be expressed in any part of the body, and it is one of the death-causing diseases. Human reproductive organs are commonly damaged by cancer. In particular, the women reproductive system is affected by various cancers including ovarian, cervical, endometrial, vaginal, fallopian tube, and vulvar cancers. Identifying these cancers at earlier stages prevents the damage to the organs. Aptamer is the potential probe that can identify these cancers. Aptamer is an artificial antibody selected from the randomized library of molecules and has a high binding affinity to the target biomarker. Targeting cancers in the reproductive organs using aptamers showed an excellent efficiency of detection compared to other probes. Different aptamers have been generated against the gynaecological cancer biomarkers, which include HE4, CA125, VEGF, OCCA (for ovarian cancer), EGFR, FGFR1, K-ras (for endometrial cancer), HPV E-16, HPV E-7, HPV E-6, tyrosine, and kinase (for cervical cancer), which help to identify the cancers in woman reproductive organs. In this overview, the biomarkers for gynecologic cancers and the relevant diagnosing systems generated using the specific aptamers are discussed. Furthermore, the therapeutic applications of aptamer with gynaecological cancers are narrated.